Experimental design to optimize degradation of organic compounds in wastewater from semiconductor industry using fenton reagent - Carmen Rodrigues (2008)
The aim of this work was to study the possibility of treating an industrial semiconductor wastewater by combining physical and chemical methods. The combined treatment consisted of pH adjustment to 2 followed by filtration and then chemical oxidation with Fenton reagent over the resulting filtered wastewater. In chemical oxidation treatment, the isolated effect of the variables on the degradation of the organic compounds - measured by chemical oxygen demand (COD) removal - was first studied: pH (3 to 5), reaction time (0.25 to 5 hours), hydrogen peroxide concentration (2.1 to 5.9 M) and FeSO4: H2O2 mass ratio (1:5 to 3:2). Higher COD removal (75%) was obtained when a pH value of 3, reaction time of 4 hours, hydrogen peroxide concentration of 4.2 M and FeSO4: H2O2 mass ratio of 1:5 were used. The global efficiency of COD removal by combination of the two treatments was 80%. The influence of three variables and their interactions was evaluated, using an experimental design of the type 23. The design also allowed the conclusion that reaction time has a statistical meaning.